Ovarian mucinous borderline tumor with anaplastic carcinomatous nodules in adolescents - Mengqi Huang; Qian Lv; Jingyan Xie (BMC, 2022)
Abstract Bilateral ovarian epithelial neoplasms in adolescents are rare. Moreover, borderline mucinous neoplasms with local intraepithelial carcinoma with anaplastic carcinoma are even more infrequent. Herein, we presented a single case (a 17-year-old female) with regular menstrual cycles and stomach pain when eating who was diagnosed with a left ovarian tumor accompanied by mural nodules. The right ovarian cyst, the left ovary, and the fallopian tube were removed by surgery. Intraoperative diagnosis suggested a bilateral ovarian tumor with mural nodules, which include three different pathological types: sarcomatoid transformation, anaplastic carcinoma, and sarcoma. Paclitaxel combined with carboplatin was given for 6 cycles after an operation, and gonadotropin-releasing hormone agonist (GnRHa) was given at the beginning of chemotherapy for 3 cycles for ovarian function protection. Regular follow-up (the last follow-up was performed 48 months after the operation) of gynecological ultrasound and tumor indicators did not indicate recurrence. In clinical practice, it is necessary to pay attention to the symptoms such as abdominal pain in adolescent females. Routine non-invasive pelvic ultrasound is recommended to fully evaluate the nature of the tumor before surgery, and decide the operation mode. Also, intraoperative frozen pathology of the tissue should be performed as soon as possible.